2007
DOI: 10.1152/jn.00473.2007
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Potentiation in the Hippocampal CA1 Region Does Not Require Insertion and Activation of GluR2-Lacking AMPA Receptors

Abstract: Activity-dependent insertion of AMPA-type glutamate receptors is thought to underlie long-term potentiation (LTP) at Schaffer collateral fiber synapses on pyramidal cells in the hippocampal CA1 region. Although it is widely accepted that the AMPA receptors at these synapses contain glutamate receptor type 2 (GluR2) subunits, recent findings suggest that LTP in hippocampal slices obtained from 2- to 3-wk-old rodents is dependent on the transient postsynaptic insertion and activation of Ca(2+)-permeable, GluR2-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
86
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 21 publications
11
86
3
Order By: Relevance
“…The reason TBP-LTP is so slow to develop remains obscure but does not depend on activity after the induction protocol (5). This makes it unlikely that it is due to NMDAR or AMPAR activity after LTP induction, consistent with prior reports (17,18).…”
Section: Resultssupporting
confidence: 79%
“…The reason TBP-LTP is so slow to develop remains obscure but does not depend on activity after the induction protocol (5). This makes it unlikely that it is due to NMDAR or AMPAR activity after LTP induction, consistent with prior reports (17,18).…”
Section: Resultssupporting
confidence: 79%
“…Thus, GluR2-lacking AMPARs might keep both LTP and spine expansion in a labile state whereas switching to GluR2-containing AMPARs stabilizes both forms of modifications. However, whether GluR2-lacking AMPARs underlie LTP expression remains highly controversial (20)(21)(22).In this study, we found that perisynaptic AMPARs are GluR2-lacking and switch to GluR2-containing after translocating to synapses. No reversal of LTP could be induced when GluR2-lacking AMPARs are present at synapses indicating that they are not sufficient to support reversal.…”
mentioning
confidence: 67%
“…4A). Chel or PKCI (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) did not have any significant effects on basal synaptic transmission ( Fig. S4 A and C) or the size of naïve spines (Fig.…”
Section: Pkc Activity Is Required For the Full Expression Of Ltp But mentioning
confidence: 95%
See 1 more Smart Citation
“…Although these receptors are subsequently replaced by GluR2-containing AMPARs, their transient expression in the synapse increases Ca 2ϩ permeability, and may contribute to the stabilization of LTP (Plant et al, 2006;Lu et al, 2007b). At later developmental stages GluR2-lacking AMPARs are no longer required for the early phase of LTP (Lu et al, 2007b), which may explain the discrepancies found in the literature concerning this issue (Adesnik and Nicoll, 2007;Gray et al, 2007). Under resting conditions AMPARs are recycled in a constitutive manner between synapses and intracellular membrane compartments, where they are sorted for degradation or for reinsertion at synapses (Ehlers, 2000;Passafaro et al, 2001) (see above).…”
Section: Role Of Ampars In Ltpmentioning
confidence: 99%